THE EFFECT OF MINDFULNESS ON DIABETES MELLITUS: A SCOPING REVIEW - Aminah, Eneng; Erawati, Meira; Dwidiyanti, Meidiana (Nurse and Health: Jurnal Keperawatan, 2024)
Background: This research provides a long-term effect to find out from mindfulness intervention for conditions that require, one of which is chronic illness, in accepting the condition experienced. The prevalence of chronic diseases in the world reaches 70% of cases resulting in death. World health. The aim of this research is to determine the effect of mindfulness on diabetes. Objective: This study was conducted a scoping review Data source: in searches using databases, Science Direct, PubMed, Scopus, and Wiley. When searching, use the keywords '' mindfulness'' and ''diabetes''. Where in screening or filtering articles, namely marking or filtering with ''2019-2023'', ''free full text'', ''medicine'', and ''nursing''. From several databases used in this research, 11 articles were analyzed as a result of the search and analysis. Review Methods: The method used is Scoping Review, and it is guided by the PRISMA flowchart, and synthesis is carried out from the extraction. Results: Mindfulness can improve glycemic control, reduce stress levels, improve quality of life, reduce HbA1c scores , and reduce the hormone cortisol. Conclusion: The results of the review show that the effect of mindfulness on diabetes mellitus can reduce psychological stress such as stress, depression, and reduce the hormone cortisol, and increase feelings of happiness and reduce blood glucose levels in patients with type 1 diabetes and type 2 diabetes.